Palgrave dictionary of public order policing, protest and political violence - Joyce, Peter (Palgrave Macmillan, 2014)
Machine generated contents note: -- About the Editors List of Entries Editors' IntroductionPalgrave Dictionary of Public Order Policing, Protest and Political ViolenceIndex